The Use of Mobile Applications in Digital Project-based Learning to Improve Students’ English Speaking Skill - Woro Kusmaryani; Firima Zona Tanjung (Script Journal: Journal of Linguistics and English Teaching, 2023)
Background: For Indonesian teachers and students alike, learning to speak English is still a significant difficulty. The use of media, especially mobile applications in English language learning can help draw in learners, boost motivation, and encourage creativity. Methodology: Convergent parallel mixed-methods was employed with 40 students as participants in this research. The data used was tests, documents, observation, and interview which analyzed quantitatively and qualitatively through statistical Wilcoxon signed ranks test, coding, and thematic analysis. Findings: Mobile applications used in this research were YouTube, Tiktok, Instagram, Duolingo, Talk, Elsa, Seesaw, Cake, Pixton, Speech to Text, and Capcut. The implementation process was divided into 5 stages; planning stage, implementation stage, evaluation stage, reflection stage, and follow-up stage. The pre-test and post-test results showed that the value of the asymptotic sign (2-tailed) 0.000 < 0.05 indicated that the use of mobile applications could greatly enhance students' speaking skill. The students’ perception showed that mobile applications in the classroom made learning more convenient, students could use them to practice English skills, complete assignments, find out information, or even receive the materials their lecturers offer them. Conclusion: The use of technology, such as mobile applications, can be a useful aid in the study of the English language, giving students more exposures, practices, and individualized instructions. Originality: This research reveals the implementation, effectiveness, and students' perceptions of mobile applications used in digital project-based learning. It is possible to maximize the benefits and minimize the drawbacks.